KETENTUAN AYAT-AYAT RIBA, TAFSIRNYA DAN FATWA RIBA - Nasrul Amanu (Institut Agama Islam Agus Salim Metro Lampung, 2022)
This research aimed to obtain the description on how the application of revenue sharing in BTM KSU Sejahtera of UMP (University of Muhammadiyah Purwokerto) whether or not it has been in accordance with provision of Muamalah Fiqh. This research used qualitative approach. Whereas techniques of data collection were: interview, observation, and documentation. The data analysis was descriptive analysis through three procedures; data reduction, data presentation, and conclusion. Then the data were analyzed qualitatively. The research result indicated; technically or in axiological way, revenue sharing application in BTN KSU Sejahtera UMP has not been fully in accordance with provision of mudharabah and revenue sharing in fiqh of muamalah.